"k^2+3k+2=0"
"k_1=-2"
"k_2=-1"
"y(x)=C_1e^{k_1x}+C_2e^{k_2x}"
"y(x)=C_1e^{-2x}+C_2e^{-x}"
"e^{-x}\\frac {d}{dx}C_2(x)+e^{-2x}\\frac {d}{dx}C_1(x)=0"
"\\frac {d}{dx}(e^{-x})\\frac {d}{dx}C_2(x)+\\frac {d}{dx}(e^{-2x})\\frac {d}{dx}C_1(x)=sin(e^x)"
"e^{-x}\\frac {d}{dx}C_2(x)+e^{-2x}\\frac {d}{dx}C_1(x)=0"
"-e^{-x}\\frac {d}{dx}C_2(x)-2e^{-2x}\\frac {d}{dx}C_1(x)=sin(e^x)"
"\\frac {d}{dx}C_1(x)=-e^{2x}sin(e^x)"
"\\frac {d}{dx}C_2(x)=e^{x}sin(e^x)"
"C_1(x)=-\\int e^{2x}sin(e^x)dx=e^xcos(e^x)-sin(e^x)+C_3"
"C_2(x)=\\int e^{x}sin(e^x)dx=C_4-cos(e^x)"
Answer:
"y(x)=C_3e^{-2x}+C_4e^{-x}-e^{-2x}sin(e^x)"
Comments
Leave a comment